Orchard Establishment Budget for Peaches and Nectarines in Florida - Mercy Olmstead; Kim Morgan (EDIS, 2013)
Stone fruit production in Florida, specifically peaches (Prunus persica L.), has increased in acreage since the mid-2000s, predominantly driven by the desire to diversify agricultural operations. Although the National Agriculture Statistics Service does not keep annual production and acreage statistics for peaches because of the industry’s small size, a recent poll revealed just over 670 acres in Florida, with about 700 unreported acres (Table 1) (Morgan and Olmstead 2013). Statewide, current estimates of harvested peaches are approximately 4.5 million pounds, with a value of more than $6 million. Florida growers can take advantage of an early market window in which they produce the first domestic peach of the calendar year, commanding a high price per pound. The future of peach production in the state is very positive, and many growers continue to plant new orchards. This 12-page fact sheet was written by Mercy Olmstead and Kim Morgan, and published by the UF Department of Horticultural Sciences, July 2013.